Determination of Interleukin 31 (IL-31) serum levels according to severity of allergic rhinitis (Bangladesh Journal of Medical Science, 2015)
Objective: This study was conducted to compare IL-31 serum levels in allergic rhinitis (AR) patients and normal controls as well as according to severity of AR. Materials and Methods: The subjects, normal controls and AR patients, were defined by history taking. Blood were collected from subjects and patients with AR. Serum was centrifuged and analyzed for IL-31 using enzyme linked immunosorbent assay (ELISA) kits. 70 samples of normal controls and 70 samples of AR were collected respectively. Results and Discussion: The result showed that IL-31 serum level was higher in allergic rhinitis patients, mean (SD) 4107.70 (16961.51) as compared with normal controls 2195.55 (9016.57), however it was not statistically significance with p-value, 0.406 by using independent-T test. The result also showed no significant difference of IL-31 levels according to severity of AR with p-value, 0.245 by using Mann-Whitney test. Conclusions: IL-31 serum level was higher in AR patients; however it was not statistically significant. There was also no significant difference of IL-31 levels between the severity of AR. Further study which obtain the larger sample sizes should be done to get better findings.Bangladesh Journal of Medical Science Vol.14(4) 2015 p.359-362